2014
DOI: 10.3390/ijms150813437
|View full text |Cite
|
Sign up to set email alerts
|

Hip Osteoarthritis in Dogs: A Randomized Study Using Mesenchymal Stem Cells from Adipose Tissue and Plasma Rich in Growth Factors

Abstract: Purpose: The aim of this study was to compare the efficacy and safety of a single intra-articular injection of adipose mesenchymal stem cells (aMSCs) versus plasma rich in growth factors (PRGF) as a treatment for reducing symptoms in dogs with hip osteoarthritis (OA). Methods: This was a randomized, multicenter, blinded, parallel group. Thirty-nine dogs with symptomatic hip OA were assigned to one of the two groups, to receive aMSCs or PRGF. The primary outcome measures were pain and function subscales, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
116
0
9

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(136 citation statements)
references
References 75 publications
6
116
0
9
Order By: Relevance
“…All these in vivo studies support their therapeutic potential, although variably Hall, Rosenkrantz, Hong, Griffin, & Mendelsohn, 2010;Kim et al, 2011;Muir et al, 2016;Sousa et al, 2011). Majority of the studies have not reported any major adverse effect (Black et al, 2007(Black et al, , 2008Cuervo et al, 2014;Pérez-Merino, Usón-Casaús, Zaragoza-Bayle, et al 2015a;Bçrziòð et al, 2018;Villatoro et al, 2015), except for few studies wherein reactions like selfcontrollable localized inflammation and pulmonary parenchymal edema and hemorrhage have been reported (Kang & Park, 2014;Mokbel et al, 2011;Park et al, 2012b). Apart from varied systemic ailments, recent study showed that dMSCs can control chronic bacterial infection.…”
Section: In Vivo Potential Therapeutic Applicationsmentioning
confidence: 99%
“…All these in vivo studies support their therapeutic potential, although variably Hall, Rosenkrantz, Hong, Griffin, & Mendelsohn, 2010;Kim et al, 2011;Muir et al, 2016;Sousa et al, 2011). Majority of the studies have not reported any major adverse effect (Black et al, 2007(Black et al, , 2008Cuervo et al, 2014;Pérez-Merino, Usón-Casaús, Zaragoza-Bayle, et al 2015a;Bçrziòð et al, 2018;Villatoro et al, 2015), except for few studies wherein reactions like selfcontrollable localized inflammation and pulmonary parenchymal edema and hemorrhage have been reported (Kang & Park, 2014;Mokbel et al, 2011;Park et al, 2012b). Apart from varied systemic ailments, recent study showed that dMSCs can control chronic bacterial infection.…”
Section: In Vivo Potential Therapeutic Applicationsmentioning
confidence: 99%
“…OA which is one of the most prevalent disease in companion animals was addressed in several veterinary stem cell‐based clinical trials (Table ). Four of five stem cell trials focused on canine hip and one on canine elbow OA (loci of highest prevalence), and all trials employed single injections of intra‐articular AD‐MSC. AD‐MSC was used alone , or in conjunction with either intra‐articular autologous platelets rich in growth factors (PrP) or hyaluronic acid (HA) as a chondroprotective agent (Table ) Comparisons were made between cultured AD‐MSC plus PrP versus AD‐MSC plus HA , or AD‐MSC versus fresh stromal vascular fraction (SVF) .…”
Section: Study Disease Targetsmentioning
confidence: 99%
“…Blind force plate analysis, considered the gold standard in objective gait analysis, was performed in two of five of the canine OA studies [106,107]. Only one study employed a double blind randomized controlled study design [108], and none of the studies employed placebo controls. The studies consistently demonstrated improved endpoints (pain, ROM, VAS) in dogs treated with AD-MSC, AD-MSC plus PrP, AD-MSC plus HA, or SVF.…”
Section: Study Disease Targetsmentioning
confidence: 99%
“…MSCs have also been widely used for treatment of osteoarthritis in dogs, a progressive degenerative condition that also has an associated inflammatory component. Studies of canine adiposederived MSC (Ad-MSC) and bone marrow-derived MSC (BM-MSC) injected into the elbow and hip joints of dogs with osteoarthritis produced positive results in terms of improvement in clinical measures of osteoarthritis reported in most investigations [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%